Neuropathologic features of central nervous system hemangioblastoma - Rebecca A. Yoda; Patrick J. Cimino (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Hemangioblastoma is a benign, highly vascularized neoplasm of the central nervous system (CNS). This tumor is associated with loss of function of the VHL gene and demonstrates frequent occurrence in von Hippel-Lindau (VHL) disease. While this entity is designated CNS World Health Organization grade 1, due to its predilection for the cerebellum, brainstem, and spinal cord, it is still an important cause of morbidity and mortality in affected patients. Recognition and accurate diagnosis of hemangioblastoma is essential for the practice of surgical neuropathology. Other CNS neoplasms, including several tumors associated with VHL disease, may present as histologic mimics, making diagnosis challenging. We outline key clinical and radiologic features, pathophysiology, treatment modalities, and prognostic information for hemangioblastoma, and provide a thorough review of the gross, microscopic, immunophenotypic, and molecular features used to guide diagnosis.